The Ethics of Karbala: Myths, Modernity, and Virtues of Nobility - Syeda Dur e Nayab Haider (Muslim Politics Review, 2026)
The Ethics of Karbala: Myths, Modernity, and Virtues of Nobility by Cyrus Ali Zargar is an intellectually rich and deeply moving thinking on the way the memory of the Battle of Karbala is still shaping Islamic ethical consciousness. Published in 2024, the book is one of the exemplars of the new generation of interdisciplinary Islamic studies that integrate traditional Islamic scholasticism, modern philosophy, literary criticism, and theology. Although the battle of Karbala is among the most passionately observed and emotionally charged events in the history of Islam, the book of Zargar does not just do that; he puts the story not merely as a historical tragedy, or a matter of theological argument, but as a source of ethics, as an element of life. It encourages the reader to consider virtue as a tradition, not something abstracts as a goal but practiced in the body to be aroused by recollection, ritual, poetry, and politics.